Amelioration of Chromium-Induced Oxidative Stress by Combined Treatment of Selected Plant-Growth-Promoting Rhizobacteria and Earthworms via Modulating the Expression of Genes Related to Reactive Oxygen Species Metabolism in Brassica juncea - Sharma, Pooja; Chouhan, Rekha; Bakshi, Palak; Gandhi, Sumit G.; Kaur, Rupinder; Sharma, Ashutosh; Bhardwaj, Renu (Frontiers in Microbiology, 2022)
Chromium (Cr) toxicity leads to the enhanced production of reactive oxygen species (ROS), which are extremely toxic to the plant and must be minimized to protect the plant from oxidative stress. The potential of plant-growth-promoting rhizobacteria (PGPR) and earthworms in plant growth and development has been extensively studied. The present study was aimed at investigating the effect of two PGPR (Pseudomonas aeruginosa and Burkholderia gladioli) along with earthworms (Eisenia fetida) on the antioxidant defense system in Brassica juncea seedlings under Cr stress. The Cr toxicity reduced the fresh and dry weights of seedlings, enhanced the levels of superoxide anion (O2•–), hydrogen peroxide (H2O2), malondialdehyde (MDA), and electrolyte leakage (EL), which lead to membrane as well as the nuclear damage and reduced cellular viability in B. juncea seedlings. The activities of the antioxidant enzymes, viz., superoxide dismutase (SOD), guaiacol peroxidase (POD), ascorbate peroxidase (APOX), glutathione peroxidase (GPOX), dehydroascorbate reductase (DHAR), and glutathione reductase (GR) were increased; however, a reduction was observed in the activity of catalase (CAT) in the seedlings under Cr stress. Inoculation of the PGPR and the addition of earthworms enhanced the activities of all other antioxidant enzymes except GPOX, in which a reduction of the activity was observed. For total lipid- and water-soluble antioxidants and the non-enzymatic antioxidants, viz., ascorbic acid and glutathione, an enhance accumulation was observed upon the inoculation with PGPR and earthworms. The supplementation of PGPR with earthworms (combined treatment) reduced both the reactive oxygen species (ROS) and the MDA content by modulating the defense system of the plant. The histochemical studies also corroborated that the combined application of PGPR and earthworms reduced O2•–, H2O2, lipid peroxidation, and membrane and nuclear damage and improved cell viability. The expression of key antioxidant enzyme genes, viz., SOD, CAT, POD, APOX, GR, DHAR, and GST showed the upregulation of these genes at post-transcriptional level upon the combined treatment of the PGPR and earthworms, thereby corresponding to the improved plant biomass. However, a reduced expression of RBOH1 gene was noticed in seedlings supplemented under the effect of PGPR and earthworms grown under Cr stress. The results provided sufficient evidence regarding the role of PGPR and earthworms in the amelioration of Cr-induced oxidative stress in B. juncea.